2006
DOI: 10.1016/j.lfs.2006.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Decreased α2-adrenergic receptor in the brain stem and pancreatic islets during pancreatic regeneration in weanling rats

Abstract: Sympathetic stimulation inhibits insulin secretion. a2-Adrenergic receptor is known to have a regulatory role in the sympathetic function. We investigated the changes in the a2-adrenergic receptors in the brain stein and pancreatic islets using [3H]Yohimbine during pancreatic regeneration in weanling rats. Brain stem and pancreatic islets of experimental rats showed a significant decrease (p<0.001) in norepinephrine (NE) content at 72 h after partial pancreatectomy. The epinephrine (EPI) content showed a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…A role for adrenergic receptors in the activation of intracellular signalling pathways that lead to mitogenic responses has been described [18,23,24], whilst abnormalities of sympathetic effects, including disturbances of leptin and β3-adrenergic receptor signalling may contribute to the development of obesity and type 2 diabetes in rodents [25]. We hypothesize that the exaggerated leptin surge [17] and increased sympathetic drive [19] we observe in offspring of obese rodents may also contribute to altered pancreatic development post-natally and promote NAFPD in this model [26]. Importantly, increased sympathetic drive has also implicated in proliferation of pancreatic cancer cells [27,28].…”
Section: Discussionmentioning
confidence: 56%
“…A role for adrenergic receptors in the activation of intracellular signalling pathways that lead to mitogenic responses has been described [18,23,24], whilst abnormalities of sympathetic effects, including disturbances of leptin and β3-adrenergic receptor signalling may contribute to the development of obesity and type 2 diabetes in rodents [25]. We hypothesize that the exaggerated leptin surge [17] and increased sympathetic drive [19] we observe in offspring of obese rodents may also contribute to altered pancreatic development post-natally and promote NAFPD in this model [26]. Importantly, increased sympathetic drive has also implicated in proliferation of pancreatic cancer cells [27,28].…”
Section: Discussionmentioning
confidence: 56%
“…In the central system, a 2 -adrenergic receptors binding sites are existed in rat paraventricular nucleus and median eminence of hypothalamus (Pasquali et al 2000). Also a 2 -adrenergic receptors found in the olfactory tubercles, striatum and hippocampus (Sallinen et al 2007) appears to be an important modulator of noradrenergic neurotransmission (Das et al 2006). Moreover pan et al showed that a 2 -adrenergic receptors are also located in the superficial dorsal and ventral horns of the spinal cord (Pan et al 2002).…”
Section: Introductionmentioning
confidence: 99%